Neuropeptides as Therapeutic Targets to Combat Stress-Associated Behavioral and Neuroendocrinological Effects - Bali, Anjana; Singh, Nirmal; Singh Jaggi, Amteshwar (CNS & Neurological Disorders - Drug Targets, 2014)
Stress has become an integral part of human life and organisms are being constantly subjected to stress and the ability to cope with such stress is a crucial determinant of health and disease. Neuropeptides (bioactive peptides) play a crucial role in mediating different effects of acute and chronic stress. Some of these neuropeptides including oxytocin, urocortins, neuropeptide Y (NPY), neuropeptide S, cocaine and amphetamine regulated transcript, endorphins, enkephalins, ghrelin and thyrotropin-releasing hormone primarily attenuate stress and act as anxiolytic. On the other hand, neuropeptides including corticotropin releasing hormone, vasopressin, dynorphin, angiotensin, nesfatin-1, orexin and cholecystokinin primarily tend to promote stress related anxiety behavior. However, these neuropeptide tend to produce different actions depending on the type of receptors, the nature and intensity of the stressor. For example, NPY may exhibit anxiolytic effects by activating NPY1 and Y5 receptors, while pro-depressive effects are produced through NPY2 and Y4 receptors. Galanin may produce ‘prodepressive’ effects by activating its Gal 1 receptors and exert ‘antidepressant’ effects through Gal 2 receptors. The present review describes different neuropeptides as therapeutic targets to attenuate stress-induced behavioral and neuroendocrinological effects.
Keywords: Stress